Parents' information needs and influential factors when making decisions about TNF-α inhibitors. Issue 1 (December 2016) - Lipstein, Ellen; Lovell, Daniel; Denson, Lee; Kim, Sandra; Spencer, Charles; Britto, Maria
Abstract Background Parents struggle when making treatment decisions for children with arthritis or other chronic conditions. Understanding their decision-making process is an essential step towards improving the decision-making experience. The objective of this study was to describe parents' information needs and the influences on their decision making about treatment with TNF-α inhibitors. Methods Survey domains were developed based on qualitative data and cognitive interviewing. We mailed the survey to parents of children with juvenile idiopathic arthritis or inflammatory bowel disease who had initiated treatment with TNF-α inhibitors in the prior 2 years. Data were analyzed using descriptive and non-parametric statistics. Results Survey response rate was 54.9 %. Each item had <2 % missing responses. Parents used an array of information sources when deciding about treatment with TNF-α inhibitors. Resources other than their child's specialist were most often used to increase confidence in parents' decisions or because they wanted to know more about other people's experiences being treated with TNF-α inhibitors, rather than due to a lack of understanding. All but two (cost and route of administration) of the influential decision factors were very or extremely important to the majority of participants with factors related to long-term side effects, treatment efficacy, and disease impact being most important. Conclusions This study describes parents' information needs and influential factors in treatment decision making. Results suggest that future work should be aimed at helping families weigh risks and benefits, such as through decision support interventions, as well as developing opportunities to include people beyond the family and physician in the decision-making process.